STRATEGI SOCIAL MARKETING DALAM EDUKASI KOMUNIKASI KRISIS BENCANA ALAM BAGI STAKEHOLDER KEPARIWISATAAN TANJUNG LESUNG - Adinda Tresna Dewi, - (2022)
ABSTRACT Adinda Tresna Dewi, 1808121. "Social Marketing Strategy in Communication Education During the Crisis of Natural Disasters for Tanjung Lesung Tourism Stakeholders" under the guidance Bagja Waluya, S.Pd., M.Pd and Ilma Indriasri Pratiwi,SE.,MP.Par. With the occurrence of natural disasters, hard work is needed. Communication of the tourism crisis during the Sunda Strait tsunami disaster is an effort taken to restore the trust of outsiders. For this reason, various prevention efforts are needed before a disaster, mitigation and recovery of initial conditions after a natural disaster between stakeholders, and a clear, well-planned crisis communication and coordination system is needed regarding the post-disaster recovery process. This research method uses a qualitative approach with a qualitative exploratory method. In-depth data collection techniques used in this research are in-depth interviews and documentation. The data analysis used is data collection, data reduction, data presentation and conclusion drawing. The results showed that the disaster crisis communication was carried out by the government to minimize the impact of the disaster. This crisis communication was carried out with a special crisis communication team centered on the BPBD of Pandeglang Regency at the time of the disaster communication incident. coordination between groups to run optimally. Crisis communication at each stage of a disaster has been carried out optimally, such as socializing disaster preparedness and mitigation. Tanjung Lesung also has a device that can read wave pressure. Waves, Earthquake vibrations. Training is carried out for local communities prone to natural disasters, and tourists are carried out routinely and gradually. Keywords: Crisis Communication, Social Marketing, Tanjung Lesung, Natural Disaster